Peran sasaran kinerja pegawai (skp) dan sertifikasi terhadap kinerja pustakawan - Khairina Hazrati (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2017)
This article discusses about Employee performance and certification performance targets on the performance of librarians. Performance Performance Librarians, both within the government and private sphere at this time, are absolute considering that the role of librarians today has changed, from librarians who simply keep and manage books transformed into managing information. At this time information is very fast, so with the (Unit Performance Employees) can see how effective the performance of an employee. Keywords: Employee, performance, certification.